2019
DOI: 10.1155/2019/7958701
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Potential ofSargassum muticumagainst STZ-Induced Diabetic Liver Damage in Wistar Rats by Inhibiting Cytokines and the Apoptosis Pathway

Abstract: Liver inflammation and necrosis are the foremost problems interlinked with diabetes mellitus (DM). The methanolic extract of Sargassum muticum (MESM) plays a hepatoprotective role in streptozotocin- (STZ-) induced hepatic injury. In this study, STZ exposure induced diabetes that augmented hepatic damage, which was reflected in serum enzyme markers, the cytokine network, and caspase-3 and caspase-9 levels in Group 2. Exposure to the MESM tremendously modulated the levels of hepatic enzyme markers ALP, ACP, ALT,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 31 publications
4
10
0
Order By: Relevance
“…The secretion of abnormal levels of liver function enzymes in the blood are vital indicators of liver injury in DM. ALT, AST and ALP levels have been shown to be increased in hepatic insulin resistance and T2DM . In this study, SRL significantly reduced the level of these biomarkers of liver injury in the treated diabetic rats.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The secretion of abnormal levels of liver function enzymes in the blood are vital indicators of liver injury in DM. ALT, AST and ALP levels have been shown to be increased in hepatic insulin resistance and T2DM . In this study, SRL significantly reduced the level of these biomarkers of liver injury in the treated diabetic rats.…”
Section: Discussionsupporting
confidence: 56%
“…ALT, AST and ALP levels have been shown to be increased in hepatic insulin resistance and T2DM. [28,29] In this study, SRL significantly reduced the level of these biomarkers of liver injury in the treated diabetic rats.…”
Section: Identification Of Chemical Constituentssupporting
confidence: 54%
“…Some studies have shown that curcumin protects astrocytes from oxidative stress, thus potentially using them for treating various neurodegenerative diseases [51]. In addition, DM is highly correlated with liver inflammation, cirrhosis, apoptosis, and ultimately causes liver malfunction [52].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that curcumin protects astrocytes from oxidative stress, thus potentially using them for treating various neurodegenerative diseases [39]. In addition, DM is highly correlated with liver inflammation, cirrhosis, apoptosis, and ultimately causes liver malfunction [40]. The results of our experiment showed that a high-fat diet combined with streptozotocin treatment significantly upregulated MDA levels and significantly downregulated SOD levels in experimental rats.…”
Section: Discussionmentioning
confidence: 51%